A new species of Pseudohelicoon (Tubeufiales, Dothideomycetes) from Taiwan - Goh, Teik-Khiang; Hsieh, Sung-Yuan; Kuo, Chang-Hsin (Phytotaxa, 2024)
Pseudohelicoon ellipsoideum sp. nov. from a decaying rachis of an unidentified palm submerged in a freshwater stream at Linmei-Shipan Trail, Taiwan, is described and illustrated. The phylogeny of Pseudohelicoon and other Helicoon species (sensu lato) was inferred by a concatenated dataset of the ITS and partial LSU segments of the nuc rDNA. The new species is phylogenetically positioned among the other two previously described species of Pseudohelicoon, but morphologically it differs from them in the shape and size of conidia.